UPAYA GURU DALAM MENGATASI DISGRAFIA (KESULITAN MENULIS) PADA SISWA KELAS RENDAH - Vera Ironita Christiani Sihombing; Rahman; Vismaia Sabariah Damaianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article focuses on the teacher's efforts in overcoming dysgraphia (writing difficulties) for at the low-class level. The study in this article refers to the teacher's efforts in overcoming the students’ dysgraphia (writing difficulties). The method used is a case study with a qualitative approach. The results of the study were a description descriptively. The sources of data in this study were teachers who were certified and had or were currently dealing with dysgraphia children. Data collection were data triangulation like observation, interviews, and documentation. The instrument used was a questionnaire which was distributed and filled in through the Google Form application.